Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1073/pnas.86.13.5183
|View full text |Cite
|
Sign up to set email alerts
|

Visual responses in adult cat visual cortex depend on N-methyl-D-aspartate receptors.

Abstract: We have investigated the role of the N-methyl-D-aspartate (NMDA) receptor, a subtype of glutamate receptor, in the responses of cells in adult cat visual cortex. After intracortical infusion of the NMDA receptor antagonist DL-2-amino-5-phosphonovalerate (DL-APV) for one day, iontophoretic responses to NMDA, to kainate, and to quisqualate revealed a receptor blockade specific to NMDA receptors and extending several millimeters from the cannula. In this region, neuronal responses to visual stimulation were profo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
86
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(99 citation statements)
references
References 32 publications
13
86
0
Order By: Relevance
“…We found, in contrast, that NMDA receptors participate strongly in normal sensory responses in the barn owl's ICx. Similar results have been found in a variety of in vivo preparations, including the striate cortex (Tsumoto et al, 1987;Fox et al, 1989;Miller et al, 1989) somatosensory cortex (Armstrong-James et al, 1993) lateral geniculate nucleus Kwon et al, 1991Kwon et al, , 1992 and ventrobasal thalamus (Salt, 1987;Salt andEaton, 1989, 1991;Eaton and Salt, 1990). Together these data indicate that in many intact preparations, NMDA receptors can participate strongly in normal sensory transmission (for review, see Nelson and Sur, 1992;Daw et al, 1993).…”
Section: Nmda Receptors Mediate Auditory Responses In the Icxsupporting
confidence: 64%
“…We found, in contrast, that NMDA receptors participate strongly in normal sensory responses in the barn owl's ICx. Similar results have been found in a variety of in vivo preparations, including the striate cortex (Tsumoto et al, 1987;Fox et al, 1989;Miller et al, 1989) somatosensory cortex (Armstrong-James et al, 1993) lateral geniculate nucleus Kwon et al, 1991Kwon et al, , 1992 and ventrobasal thalamus (Salt, 1987;Salt andEaton, 1989, 1991;Eaton and Salt, 1990). Together these data indicate that in many intact preparations, NMDA receptors can participate strongly in normal sensory transmission (for review, see Nelson and Sur, 1992;Daw et al, 1993).…”
Section: Nmda Receptors Mediate Auditory Responses In the Icxsupporting
confidence: 64%
“…An alternative explanation is that NMDARs could play a critical role in action potential generation and that the stimulation pattern is important in determining how much or how little a role. Supporting this idea is the observation that NMDAR antagonists can inhibit cell firing in the visual system (Miller et al, 1989;Sillito et al, 1990;Blitz and Regehr, 2003) (but see Bear et al, 1990) and in the hippocampus, as assessed by population spike size (Abraham and Mason, 1988;Burgard et al, 1989;Dahl et al, 1990). Here, we show that NMDARs do play a critical role in action potential generation in the hippocampal slice and that this role is dependent on stimulation pattern.…”
Section: Introductionsupporting
confidence: 51%
“…We found that the initial visual response was very sensitive to CNQX, indicating a strong contribution of AMPA-Rs, in accordance with previous studies (22,31,32). The extent to which NMDA-Rs contribute to the visually driven response is a matter of debate, because some studies reported that APV suppresses visual responses (31,33), whereas other studies found that NMDA-Rs do not contribute strongly to visually driven The data shown here were normalized by the maximum response across conditions in the predrug period. The data from the recovery period were obtained 1 h after the injection.…”
Section: Discussionmentioning
confidence: 99%